Sains sebagai Sumber Soft Power Indonesia [Science as a Source of Soft Power for Indonesia] - Ary Aprianto (Sekretariat Jenderal DPR RI, 2020)
The role of science in national development and solving global challenges has been recognized by various actors. States have also employed science as a source of soft power. However, science as a source of soft power is not popular in Indonesia. Scientific articles on the interaction between science and foreign policy are also minimal. Perhaps the fact that Indonesia’s science world still needs plenty of improvement is the reason behind this gap. This article discusses the possibility of exploring science as a source of soft power for Indonesia, utilizing qualitative research method and Geun Lee’s resource-based theory of soft power. The article concludes that science can and should be used as a source of soft power for Indonesia to support its strategic development goals, given the significant contribution of science to development in the digital era.AbstrakPeran sains dalam pembangunan nasional dan memecahkan beragam masalah global telah diakui banyak pihak. Sudah banyak negara yang memanfaatkan sains sebagai salah satu sumber soft power. Namun demikian, sains sebagai salah satu sumber soft power belum banyak dikenal di Indonesia. Tulisan ilmiah mengenai interaksi antara sains dengan politik luar negeri pun minim. Masih banyaknya hal yang perlu dibenahi dalam dunia sains nasional dapat menjadi latar belakang situasi ini. Tulisan ini mendiskusikan dapat atau tidaknya sains dimanfaatkan sebagai sumber soft power Indonesia, dengan memanfaatkan metode kualitatif dan “resource-based theory of soft power” dari Geun Lee. Disimpulkan bahwa sains dapat dan harus dimanfaatkan sebagai sumber soft power Indonesia untuk mendukung tercapainya tujuan strategis pembangunan, mengingat besarnya kontribusi sains dalam era digital.